Strategi Meningkatkan Nutrisi Makanan Bagi Masyarakat Pesisir Dan Peningkataan Ekonomi Bagi Pelaku Usaha Melalui Konsumi Produk Olahan Ikan Laut - Dedy Khaerudin; Budiharjo Budiharjo; Ganjar Sidik Gandara; Lucky Setiawan; Bambang Setyo Panulisan; M. Rizki Alfurkon; Hasanah Musstajiah; Nova Nabila; Zakia Tunavisa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Tanara Village as a Coastal Village has a potential source of food that comes from the sea, but the people around Tanara Village are still very low in consuming sea fish directly, therefore a way is needed so that the nutritional intake / nutrition consumed is able to meet the needs of the community's body. In supporting and encouraging nutritional intake, business actors have an important role to play in creating processed fish products made from marine fish with the aim of increasing appetite because they are stimulated by the results of the product variants created. Business actors must have the courage to innovate their product variants. The Lecturer Team and the KKM Group help provide solutions through assistance in terms of strategies to create innovative variants of processed seafood products for business people. This step is carried out through mentoring and training in creating flavor variants, product packaging and marketing. Another thing is that it is hoped that after the service assistance for business actors they can be more prosperous in the economic field.